2020
DOI: 10.1242/dev.190744
|View full text |Cite
|
Sign up to set email alerts
|

RAB6 GTPase regulates mammary secretory function by controlling the activation of STAT5

Abstract: The Golgi-associated RAB GTPases, RAB6A and RAB6A’, regulate anterograde and retrograde transport pathways from and to the Golgi. In vitro, RAB6A/A’ control several cellular functions including cell division, migration, adhesion and polarity. However, their role remains poorly described in vivo. Here, we generated BlgCre; Rab6aF/F mice presenting a specific deletion of Rab6a in the mammary luminal secretory lineage during gestation and lactation. Rab6a loss severely impaired the differentiation, maturation and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 60 publications
(143 reference statements)
2
10
0
Order By: Relevance
“…The Rab6A antibody applied here has previously replicated this typical vesicular perinuclear staining in Chinese hamster ovary (CHO) cells [ 41 ]. To our knowledge, however, immunocytochemical localization of Rab6A or B in mammalian tissues has been determined only by very few studies (e.g., [ 25 , 39 , 41 , 42 , 43 ], see above), including the present one.…”
Section: Discussionmentioning
confidence: 85%
“…The Rab6A antibody applied here has previously replicated this typical vesicular perinuclear staining in Chinese hamster ovary (CHO) cells [ 41 ]. To our knowledge, however, immunocytochemical localization of Rab6A or B in mammalian tissues has been determined only by very few studies (e.g., [ 25 , 39 , 41 , 42 , 43 ], see above), including the present one.…”
Section: Discussionmentioning
confidence: 85%
“…25 Moreover, several studies clearly show that absence of the endosome-to-TGN retrograde trafficking strongly perturbs the secretory process and directs proteins and lipids for lysosomal degradation. 27,[37][38][39]63 Notably, these factors are important research objects in this present study as well and were proven to also have a function in avoiding immature secretory granules from early acidification and crinophagic degradation.…”
Section: Localization Of the Endosome-to-tgn Retrograde Transport Com...mentioning
confidence: 79%
“…35,36 Importantly, earlier studies clearly showed that components of the endosome-to-TGN retrograde transport, such as Vps52, Vps53 and Rab6 are also needed for normal secretory process. [37][38][39] Degradation of unnecessary, obsolete, or damaged secretory granules is required for maintaining homeostatic equilibrium in gland cells and tissues. There are several possibilities for their elimination, depending mainly on granule size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we wanted to better characterize the role of molecules that we previously described as regulators of LAT recruitment to the immune synapse. This was particularly important for the small Rab GTPase Rab6, which has been shown to control both retrograde and anterograde transport of cargoes [ 23 , 24 , 42 , 43 , 44 ]. Yet, TIRF video-microscopy did not show any association of Rab6 and LAT at the activation sites ( Figure 3 A and Supplementary Video S3 ).…”
Section: Discussionmentioning
confidence: 99%